Characterization of LytA-Like N-Acetylmuramoyl-l-Alanine Amidases from Two New Streptococcus mitis Bacteriophages Provides Insights into the Properties of the Major Pneumococcal Autolysin - Romero, Patricia (American Society for Microbiology, 2004)
Two new temperate bacteriophages exhibiting a Myoviridae (φB6) and a Siphoviridae (φHER) morphology have been isolated from Streptococcus mitis strains B6 and HER 1055, respectively, and partially characterized. The lytic phage genes were overexpressed in Escherichia coli, and their encoded proteins were purified. The lytA(HER) and lytA(B6) genes are very similar (87% identity) and appeared to belong to the group of the so-called typical LytA amidases (atypical LytA displays a characteristic two-amino-acid deletion signature). although they exhibited several differential biochemical properties with respect to the pneumococcal LytA, e.g., they were inhibited in vitro by sodium deoxycholate and showed a more acidic pH for optimal activity. However, and in sharp contrast with the pneumococcal LytA, a short dialysis of LytA(HER) or LytA(B6) resulted in reversible deconversion to the low-activity state (E-form) of the fully active phage amidases (C-form). Comparison of the amino acid sequences of LytA(HER) and LytA(B6) with that of the pneumococcal amidase suggested that Val(317) might be responsible for at least some of the peculiar properties of S. mitis phage enzymes. Site-directed mutagenesis that changed Val(317) in the pneumococcal LytA amidase to a Thr residue (characteristic of LytA(B6) and LytA(HER)) produced a fully active pneumococcal enzyme that differs from the parental one only in that the mutant amidase can reversibly recover the low-activity E-form upon dialysis. This is the first report showing that a single amino acid residue is involved in the conversion process of the major S. pneumoniae autolysin. Our results also showed that some lysogenic S. mitis strains possess a lytA-like gene, something that was previously thought to be exclusive to Streptococcus pneumoniae. Moreover, the newly discovered phage lysins constitute a missing link between the typical and atypical pneumococcal amidases known previously.